Malignancies in Immunoglobulin G4-related ophthalmic disease. Issue 1 (January 2023) - Lai, Kenneth K.H.; Li, Emmy Y.M.; Chan, Regine Y.C.; Wong, Kenneth C.W.; Yu, Jimmy K.S.; Cheuk, W.; Hui, Y.H.; Cheng, Andy C.O.; Chin, Joyce K.Y.; Ip, S. K.; Chan, W. H.; Kwok, Jeremy S.W.; et al.
Purpose: Clinical phenotypes in Immunoglobulin G4-related disease (IgG4-RD) according to the patterns of affecting organs have different risks of malignancies. We attempt to determine the association of malignancies with IgG4-related ophthalmic disease (IgG4-ROD). Design: Retrospective cohort study. Methods: Review of medical records, orbital images and histopathology reports in a territory-wide cohort of biopsy proven IgG4-ROD patients from 2005–2019. Findings: Among 122 patients who had biopsies taken from adnexal lesions including lacrimal glands (n = 108), orbital mass (n = 30), infiltrated orbital fat (n = 10), conjunctiva (n = 2) or extraocular muscles (n = 3), 13% (16/122) developed malignancies over 73 ± 48months' follow-up. There were 9 cases of ocular adnexal lymphoma (OAL) and 7 extra-orbital malignancies. Compared with the general population, the incidence of OAL was significantly higher (standardized incidence ratios, SIRs = 10.0, 95%CI = 4.5–17.6) while that of extra-orbital malignancies was similar. The SIRs was highest within the first year (SIR = 46.7, 95%CI = 18.5–87.6) when 7 OAL were concomitantly diagnosed. Patients who developed OAL or extra-orbital malignancies were older than other patients at IgG4-ROD diagnosis (64.9 ± 7.1, 68.3 ± 8.5 versus 55.2 ± 15.0 years, P < 0.05). Asymmetric lacrimal gland enlargement (78% versus 13%), lack of frontal (0% versus 12%) or infraorbital nerve enlargement (0% versus 36%) were associated with OAL (all P < 0.05). Pre-treatment serum IgG4 level or extra-orbital IgG4-RD involvement was similar among patients with or without malignancies. Conclusion: In this biopsy-proven IgG4-ROD cohort, 7% developed OAL which was 10 times higher than the general population. Patients with asymmetric lacrimal gland enlargement or without trigeminal nerves involvement radiologically were associated with OAL.